Attendant lords: Bairam Khan and Abdur Rahim courtiers & poets in Mughal India - "Raghavan, T. C. A." (Noida, 2017)
Bairam Khan and his son, Abdur Rahim Khan-i-Khanan were soldiers, poets and courtiers whose lives reflected the turbulent times they lived in. In telling their stories, Attendant Lords spans the reigns of four emperors - Babur, Humayun, Akbar and Jahangir
Keywords: "Khan, Bairam, - 1524?-1561."